Feasibility and Limits of Magnetically Labeling Primary Cultured Rat T Cells with Ferumoxides Coupled with Commonly Used Transfection Agents - Cedric Berger; Martin Rausch; Philipp Schmidt; Markus Rudin (Molecular Imaging)
Visualization and quantification of inflammatory processes is of high importance for early diagnosis of a multitude of diseases. Magnetic resonance imaging (MRI) using iron oxide (FeO) nanoparticles as contrast agents allows the study of macrophage infiltration during inflammation in a variety of tissues. Macrophages are effectors of the immune response, their appearance being orchestrated by activated T lymphocytes. Therefore, tracking of labeled T lymphocytes, which initiate the immune process, should enable earlier detection of tissue inflammation. In this study, we investigate the feasibility of specifically labeling harvested T cells by using dextran-coated FeO nanoparticles and commonly available transfection agents (TAs). Physicochemical properties of the newly formed FeO/TA vesicles were determined as well as their cell toxicity and their T cell activation potential. The labeling efficiency of each FeO/TA combination was evaluated by measuring the transverse MRI relaxation rate R 2 by X-ray spectroscopy and magnetic selection. Toxicity and labeling efficacy differed significantly among TAs. The best results were achieved by using polyamine TAs and in particular by using poly- l -lysine at a concentration of 1.5 µg/mL administered in combination with 22.5 µg iron/mL. By using this protocol, up to 60% of harvested T cells could be labeled. Microscopic investigation revealed FeO/TA nanoparticles not only localized within the cytoplasma of the cells but also sticking to the outer membrane surface.